Straight : constructions of heterosexuality in the cinema - Dixon, Wheeler W., 1950- (State University of New York Press, 2003)
Explores the ways that stereotypes of heterosexuality are portrayed and constructed in film.
Keywords: Man-woman relationships in motion pictures.; Sex role in motion pictures.; Masculinity in motion pictures.; Relations entre hommes et femmes au cinéma.; Rôle selon le sexe au cinéma.; Masculinité au cinéma.; PERFORMING ARTS -- Film & Video -- Reference.; Man-woman relationships in motion pictures; Masculinity in motion pictures; Sex role in motion pictures; Electronic book.